"Real decision-making is hard to find" - Swiss perinatal care providers' perceptions of and attitudes towards decision-making in birth: A qualitative study - Michael Rost; Zelda Stuerner; Paulomi Niles; Louisa Arnold (Elsevier, 2022)
Purpose: Ineffective communication and limited autonomy frequently lie at the core of negative birth experiences. Numerous studies indicate a need to improve decision-making with a deliberate shift towards person-centered care. Thus, it is imperative to study the determinants of autonomy-depriving decision-making and ineffective communication through both provider and birthing people perspectives. Our study explores providers' perceptions of and attitudes towards decision-making in birth, particularly regarding person-centeredness, autonomy, informed consent, and decision-making capacity. We conducted a qualitative interview study and employed reflexive thematic analysis. In total, 15 Swiss providers from birth hospitals and birth centers participated. Results: Analysis resulted in the development of three themes and eight subthemes. First, the "otherness of birth" encompasses providers' perception of birth as a clinical situation that is fundamentally different from other clinical situations. Second, the otherness of birth goes along with an "ethical fading", that is ethical dimensions - to some extent - fade into the background as they are obscured by various circumstances that are related to birth, birthing people, and providers. Third, the "physiology-pathology-dichotomy" describes the permeative power of this dichotomy with respect to providers' decision-making approaches and their normative weighing of ethical principles. Conclusions: Decision-making in birth is a critical factor in the actualization of autonomy and characterized by bioethical complexity. Our study reveals important insights into how autonomy-depriving decision-making and ineffective communication unfolds in birth. Our findings provide a framework for future research and yield points of leverage for enhancing decision-making in birth.